Direct Measurement of the Mass Difference between Top and Antitop Quarks - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Amer Physical Soc, 2009)
We present a measurement of the mass difference between t and (t) over bar quarks in lepton + jets final states of t (t) over bar events in 1 fb(-1) of data collected with the D0 detector from Fermilab Tevatron Collider p (p) over bar collisions at root s = 1.96 TeV. The measured mass difference of 3.8 +/- 3.7 GeV is consistent with the equality of t and (t) over bar masses. This is the first direct measurement of a mass difference between a quark and its antiquark partner.